Combat pair the evolution of Air Force-Navy integration in strike warfare - Lambeth, Benjamin S. 1943- (RAND Corp., 2007)
This report documents the exceptional cross-service harmony that the U.S. Air Force and U.S. Navy have steadily developed in their conduct of integrated strike operations since the first Persian Gulf War in 1991. That close harmony contrasts sharply with the situation that prevailed throughout most of the Cold War, when the two services maintained separate and unique operating mindsets and lacked any significant interoperability features.
Includes bibliographical references
Keywords: United States -- Air Force; United States -- Navy -- Aviation; United States -- Marine Corps -- Aviation; POLITICAL SCIENCE / Political Freedom & Security / General; POLITICAL SCIENCE / Political Freedom & Security / International Security; Geschichte; Air warfare -- United States -- History; Unified operations (Military science); Marine; Luftwaffe; Kooperation; USA